Stowaway - Hesse, Karen; Parker, Robert Andrew (New York : Scholastic, 2000)
A fictionalized journal relates the experiences of a young stowaway from 1768 to 1771 aboard the Endeavor which sailed around the world under Captain James Cook.
Originally published : New York : Margaret K. McElderry Books, 2000.
Keywords: Cook, James, -- 1728-1779.; Voyages around the world -- Fiction; Diaries -- Fiction; Sea stories; Adventure stories